Live Donor Renal Transplant With Simultaneous Bilateral Nephrectomy for Autosomal Dominant Polycystic Kidney Disease Is Feasible and Satisfactory at Long-term Follow-up. Issue 2 (February 2016) - Ahmad, Sarwat B.; Inouye, Brian; Phelan, Michael S.; Kramer, Andrew C.; Sulek, Jay; Weir, Matthew R.; Barth, Rolf N.; LaMattina, John C.; Schweitzer, Eugene J.; Leeser, David B.; Niederhaus, Silke V.; Bartlett, Stephen T.; et al.
Abstract : Background: Timing of bilateral nephrectomy (BN) is controversial in patients with refractory symptoms of autosomal dominant polycystic kidney disease (APKD) in need of a renal transplant. Methods: Adults who underwent live donor renal transplant (LRT) + simultaneous BN (SBN) from August 2003 to 2013 at a single transplant center (n = 66) were retrospectively compared to a matched group of APKD patients who underwent LRT alone (n = 52). All patients received general health and polycystic kidney symptom surveys. Results: Simultaneous BN increased operative duration, estimated blood loss, transfusions, intravenous fluid, and hospital length of stay. Most common indications for BN were pain, loss of abdominal domain, and early satiety. There were more intraoperative complications for LRT + SBN (6 vs 0, P = 0.03; 2 vascular, 2 splenic, and 1 liver injury; 1 reexploration to adjust graft positioning). There were no differences in Clavien-Dindo grade I or II (39% vs 25%, P = 0.12) or grade III or IV (7.5% vs 5.7%, P = 1.0) complications during the hospital course. There were no surgery-related mortalities. There were no differences in readmission rates (68% vs 48%, P = 0.19) or readmissions requiring procedures (25% vs. 20%, P = 0.51) over 12 months. One hundred percent of LRT + SBN allografts functioned at longer than 1 year for those available for follow-up. Survey response rate was 40% for LRT-alone and 56% for LRT + SBN. One hundred percent of LRT + SBN survey responders were satisfied with their choice of having BN done simultaneously. Conclusions: Excellent outcomes for graft survival, satisfaction, and morbidity suggest that the combined operative approach be preferred for patients with symptomatic APKD to avoid multiple procedures, dialysis, and costs of staged operations. Abstract : Supplemental digital content is available in the text.